1989
DOI: 10.1111/j.1471-0528.1989.tb03353.x
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal ultrasonic assessment of endometrial growth in spontaneous and hyperstimulated menstrual cycles

Abstract: Endometrial thickness and reflectivity were a5sesced by transvaginal ultrasound in both spontaneous and hyperstimulated menstrual cycles. Two groups of women with ovulatory cycles were cxamined; women in group 1 had unexplained infertility anti women in group 2 were having artificial insemination by donor because of reduced spermatogenesis: a third group (group 3) comprised women with tuba1 infertility undergoing hyperstirnulation for in-vitro EcrtiliLation. Thcrc was no ditterence in endometrial thicknesc or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 19 publications
1
27
1
Order By: Relevance
“…Even in empirical articles that report little luteal variation in ET, a clear, though qualitative, change in ET can be observed (Figure 2, Table 6). Research measuring ET serially is infrequent, but we have found articles that document ET via transvaginal ultrasound in Canadian (Baerwald and Pierson, 2004), Scottish (Randall et al, 1989), English (Raine-Fenning et al, 2004), and Swedish populations (Bakos et al, 1994). There are a few confounding problems with the serial measurements from the literature when it comes to assessing luteal endometrial function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in empirical articles that report little luteal variation in ET, a clear, though qualitative, change in ET can be observed (Figure 2, Table 6). Research measuring ET serially is infrequent, but we have found articles that document ET via transvaginal ultrasound in Canadian (Baerwald and Pierson, 2004), Scottish (Randall et al, 1989), English (Raine-Fenning et al, 2004), and Swedish populations (Bakos et al, 1994). There are a few confounding problems with the serial measurements from the literature when it comes to assessing luteal endometrial function.…”
Section: Discussionmentioning
confidence: 99%
“…), Center for Human and Primate Reproductive Ecology (CHaPRE) (Randall et al, 1989) LH surge -6-10 depending on measurement day…”
Section: Fundingmentioning
confidence: 99%
“…Likewise, Templeton's group identified a similar sequence of changes from hypoechogenic endometrium in the follicular phase to a primarily hyperechogenic pattern in the luteal phase of stimulated cycles. 68 The sonographic changes from the follicular phase to those characteristic of the luteal phase start to be visible within 48 hours of ovulation. The hyperechoic transformation of the functional layer of the endometrium takes 4 to 7 days to complete.…”
Section: Figure 354mentioning
confidence: 98%
“…[68][69][70] Prior to ovulation, the endometrium takes on a multilayered or three line appearance formed by the echogenic basal layers and the two hypoechoic functional layers, separated by the hyperechoic interphase of the virtual uterine cavity ( Fig. 35.4).…”
Section: Endometrial Thickness: a Biomarker For Estrogen Actionmentioning
confidence: 99%
“…It is also noteworthy that endometrial thickness was not correlated with plasma E 2 levels on the day of hCG administration in the present analysis. Indeed, time‐dependent (rather than concentration‐dependent)43 thickening of the endometrium occurs throughout the follicular phase of the menstrual cycle43,45 as a probable consequence of the proliferative action of estrogens. The present data confirm the hypothesis that supraphysiological E 2 levels induced by COH do not accelerate either the pace or the magnitude of endometrial development43 beyond values triggered by physiological concentrations of estrogens.…”
Section: Uterine Receptivity: Assessing It Today (And Noninvasively)mentioning
confidence: 99%